Expanded Newborn Screening for Inborn Errors of Metabolism by Tandem Mass Spectrometry in Suzhou, China: Disease Spectrum, Prevalence, Genetic Characteristics in a Chinese Population - Wang, Ting; Ma, Jun; Zhang, Qin; Gao, Ang; Wang, Qi; Li, Hong; Xiang, Jingjing; Wang, Benjing (Frontiers in Genetics, 2019)
Abstract Expanded newborn screening for inborn errors of metabolism (IEMs) by tandem mass spectrometry (MS/MS) could simultaneously analyze more than 40 metabolites and identify about 50 kinds of IEMs. Next generation sequencing (NGS) targeting hundreds of IMEs-associated genes as a follow-up test in expanded newborn screening has been used for genetic analysis of patients. The spectrum, prevalence, and genetic characteristic of IEMs vary dramatically in different populations. To determine the spectrum, prevalence, and gene mutations of IEMs in newborns in Suzhou, China, 401,660 newborns were screened by MS/MS and 138 patients were referred to genetic analysis by NGS. The spectrum of 22 IEMs were observed in Suzhou population of newborns, and the overall incidence (excluding short chain acyl-CoA dehydrogenase deficiency (SCADD) and 3-Methylcrotonyl-CoA carboxylase deficiency (3-MCCD)) was 1/3163. The prevalence of each IEM ranged from 1/401,660 to 1/19,128, while Phenylketonuria (PKU) (1/19,128) and Mild hyperphenylalaninemia (M-HPA) (1/19,128) were the most common IEMs, followed by Primary carnitine uptake defect (PCUD) (1/26,777), SCADD (1/28,690), Hypermethioninemia (H-MET) (1/30,893), 3-MCCD (1/33,412) and Methylmalonic acidemia (MMA) (1/40,166). 89 reported mutations and 51 novel mutations in 25 IMEs-associated genes were detected in 138 patients with one of 22 IEMs. Some hot-spot mutations were observed for ten IEMs, including PAH gene c.728G>A, c.611A>G, and c.721C>T for Phenylketonuria, PAH gene c.158G>A, c.1238G>C, c.728G>A, and c.1315+6T>A for M-HPA, SLC22A5 gene c.1400C>G, c.51C>G, and c.760C>T for PCUD, ACADS gene c.1031A>G, c.164C>T, and c.1130C>T for SCAD deficiency, MAT1A gene c.791G>A for H-MET, MCCC1 gene c.639+2T>A and c.863A>G for 3-MCCD, MMUT gene c.1663G>A for MMA, SLC25A13 gene c.IVS16ins3Kb and c.852_855delTATG for cittrullinemia II, PTS gene c.259C>T and c.166G>A for Tetrahydrobiopterin deficiency, and ACAD8 gene c.1000C>T and c.286C>A for Isobutyryl coa dehydrogenase deficiency. All these hot spot mutations were reported to be pathogenic or likely pathogenic, except a novel mutation of ACAD8 gene c.286C>A. These mutational hot spots could be potential candidates for gene screening and these novel mutations expanded the mutational spectrum of IEMs. Therefore, our findings could be of value for genetic counseling and genetic diagnosis of IEMs.